If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (a + 4)(a + 5) = 0 Reorder the terms: (4 + a)(a + 5) = 0 Reorder the terms: (4 + a)(5 + a) = 0 Multiply (4 + a) * (5 + a) (4(5 + a) + a(5 + a)) = 0 ((5 * 4 + a * 4) + a(5 + a)) = 0 ((20 + 4a) + a(5 + a)) = 0 (20 + 4a + (5 * a + a * a)) = 0 (20 + 4a + (5a + a2)) = 0 Combine like terms: 4a + 5a = 9a (20 + 9a + a2) = 0 Solving 20 + 9a + a2 = 0 Solving for variable 'a'. Factor a trinomial. (5 + a)(4 + a) = 0Subproblem 1
Set the factor '(5 + a)' equal to zero and attempt to solve: Simplifying 5 + a = 0 Solving 5 + a = 0 Move all terms containing a to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + a = 0 + -5 Combine like terms: 5 + -5 = 0 0 + a = 0 + -5 a = 0 + -5 Combine like terms: 0 + -5 = -5 a = -5 Simplifying a = -5Subproblem 2
Set the factor '(4 + a)' equal to zero and attempt to solve: Simplifying 4 + a = 0 Solving 4 + a = 0 Move all terms containing a to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + a = 0 + -4 Combine like terms: 4 + -4 = 0 0 + a = 0 + -4 a = 0 + -4 Combine like terms: 0 + -4 = -4 a = -4 Simplifying a = -4Solution
a = {-5, -4}
| -132=-39 | | -(c+10)+3(2c-6)= | | -132=39 | | -3v-v=16 | | -9b=-117 | | 35x+9=55 | | -n+2n=4 | | -8b=-117 | | -7x-3=4 | | 6n-7=2n+17 | | 11x-4x^2-344= | | 1/3(s-2)=s+4 | | (x+9)(x+9)=18 | | 344=11x-4x^2 | | 3(2z-1)=6z+5 | | -28=-7(1-8b)-5(4b-3) | | (x-2)(x+3)=24 | | 32x+1=3+6 | | 2x+1+6x=81 | | -6n+9=1-8n | | -17b=-2.21 | | -17=-2.21 | | 7x-3=2x-12 | | y=-4+3x | | -34e=-3.74 | | 5x+1-7=-1 | | 25+37-2x=11 | | y=-3x+(-4) | | 8y+8=21 | | 5(9p+6)=8p | | 4x^2-6x=3 | | y=abs(x) |